Aging, Diversity, and Difference in Rural Perspective - Kimmel, Douglas (Maine Policy Review, 2015)
Recently, gender identity and sexual orientation have begun to be acknowledged as a dimension of diversity among older Mainers. Services & Advocacy for GLBT Elders (SAGE) Maine conducted a needs assessment and determined four key goals that are important for its work: provide support for GLBT elders, create networks of providers who are knowledgeable and affirmative about GLBT aging, increase opportunities for intergenerational GLBT social activities, and develop a referral networks of GLBT-affirmative long-term care facilities and resources.
Keywords: aging; diversity; gender identity; Maine; sexual orientation